Strategies for building and managing 'trust' to enable knowledge exchange at the interface of environmental science and policy. Issue 123 (September 2021) - Cvitanovic, C.; Shellock, R.J.; Mackay, M.; van Putten, E.I.; Karcher, D.B.; Dickey-Collas, M.; Ballesteros, M.
Highlights: Trust is a critical pre-condition for achieving evidence-informed policy. Trust is highly dynamic and fragile, and takes time to be built. We identify 14 strategies and associated actions for building trust. We outline a five steps for repairing trust, in cases where it has been compromised. These results can assist scientists and research institutions to build trusting relationship with decision-makers. Abstract: Trust is a critical precondition underpinning successful knowledge exchange among environmental scientists and decision-makers, and thus, evidence-informed decision-making processes. While the importance of trust is well established, however, specific approaches to building, managing and maintaining trust at the interface of environmental science and policy are lacking. Here, we seek to address this gap empirically via in-depth qualitative analysis, using the International Council for the Exploration of the Sea (ICES) as a case study. Specifically, through interviews with members of the ICES secretariat and scientific community, this study aims to (i) explore the importance of trust for organisations working at the interface of environmental science and policy, (ii) identify a range of strategies that are available for building trust at the interface of science and policy, and (iii) identify specific mechanisms for trust repair in situations where trust has been compromised. Our results show that trust is an essential component of a successful relationship between environmental science and policy, although highly dynamic and fragile. For example, while considerable time and effort is required to build trust, it can be lost in only a matter of days. Further, our results show that for successful knowledge exchange, and the attainment of research impact, trust is needed on three levels: (i) trust in individuals, (ii) trust in the organisation, and (iii) trust in the process by which knowledge is generated and exchanged. We identify 14 strategies to building trust, including the need for transparency, the importance of not advocating for a specific outcome, having a clear process for developing and providing knowledge/advice, having regular contact (preferably face to face) and being able to demonstrate independence. Finally, we identify five steps to repair trust: (i) Do not become defensive, be honest that a mistake has occurred, (ii) identify, and explain, why the mistake occurred, (iii) implement measures to ensure that the mistake does not happen again, (iv) correct the mistake (e.g. by providing updated knowledge/advice), and (v) give the trust re-building process time, and ensure ongoing face to face contact throughout that time. In presenting these insights from ICES, this study seeks to provide practical and implementable strategies that can be used by environmental scientists and/or research institutions to help them foster trust with decision-makers, enable improved knowledge exchange and build capacity for evidence-informed decision-making processes.